A new species-group of Dissomphalus (Hymenoptera: Bethylidae), with description of thirteen new species - Alencar, I. D. C. C.; Azevedo, C. O. (Zootaxa, 2008)
The microstictus species-group is defined by having a latero-apical filament at the ventral ramus of the aedeagus. Thirteen new species are described and illustrated: Dissomphalus balteus, D. divaricatus, D. forceps, D. incurvatus, D. osseus, D. paululus, D. perparvus, D. perturbatus, D. perventriosus, D. pilus, D. refertus, D. signatus and D. uncus. Features of the basal portion of the dorsal body of the male genitalia are defined and described for the first time, including the basal bar, the connector and the basal plate. A key to the species of the microstictus species-group is included. A mating pair of D. uncus collected in copula is recorded and the female is described.